"Packaging logistics": promoting sustainable efficiency in supply chains. Issue 4 (29th April 2014) - García-Arca, Jesús; Carlos Prado-Prado, J.; Trinidad Gonzalez-Portela Garrido, A.
Abstract : Purpose: – The purpose of this paper is to examine the aspects of internal and external transformation that take place in each company along the supply chain when a "sustainable packaging logistics" approach is implemented. Before this can be achieved, it is necessary to identify and characterise the principal cornerstones and stages associated with this implementation. Design/methodology/approach: – In the paper the combination of "case study" and "action research" techniques have been chosen. It has been analysed the implementation of "sustainable packaging logistics" in the supply chain of Mercadona (one of the largest retailers in Spain), paying special attention to the implementation and evolution in one of its main food suppliers. Findings: – To adopt a "Sustainable Packaging Logistics" approach allows for a proactive integration of the efficiency and sustainability in supply chains. The proposal to implement "sustainable packaging logistics", based on four cornerstones and three stages of evolution is particularly significant, while contributing to improved competitiveness. This implementation constitutes an evolutionary process which is conditioned by how each area, department or company along the supply chain interpret and assess different packaging features over time. Research limitations/implications: – The model is based on a single supply chain analysis. Originality/value: – This paper may be of interest both for researchers and professionals, because the model can aid companies in improving their global vision of product and packaging design in order to jointly increase sustainability and efficiency in the supply chain.